An optoelectronic based approach for handwriting capture - Ancillao, Andrea; Galli, Manuela; Vimercati, Sara Laura; Albertini, Giorgio (Computer methods and programs in biomedicine, 2013)
Clinical practice for the evaluation of motor and cognitive capabilities often relies upon writing and drawing tests. A non-invasive method to capture handwriting and analyze data is therefore needed. In this work a method to capture motion of a pen through a mo-cap optoelectronic system was developed, which could solve the limits of systems based on graphic tablets. Four IR passive markers were placed on a pen cap. Once a pen was equipped with the cap, track of tip was computed through a numeric algorithm using the 3D coordinates of markers provided by the optoelectronic system. Some tests were performed to estimate the error in track reconstruction and to compare the new protocol with previous reconstruction methods. The results showed a higher accuracy of the new method. The new protocol also overcomes the problems related to pen grasping and marker covering that affected other methods described in the literature and permits the evaluation of writing and drawing kinematics as well as postural behaviour related to them.